Penerapan Pembiayaan Perbankan Syariah dalam Pembangunan Industri Makanan Halal di Indonesia. - Muhamad shaiful umam (MASADIR: Jurnal Hukum Islam, 2024)
This study examines the implementation of sharia banking financing in the development of the halal food industry in Indonesia. As the country with the largest Muslim population in the world, Indonesia holds significant potential for the growth of the halal food industry. Bank Syariah Indonesia (BSI) plays a crucial role in this sector by providing sharia-compliant financing that is free from interest (riba), gambling (gharar), and uncertainty (maysir). This financing not only supports halal food entrepreneurs in expanding their businesses but also ensures that all production processes adhere to halal integrity principles. Additionally, BSI contributes to the development of human resources through training programs that enhance industry capacity. The study finds that with the support of sharia financing and human resource development, BSI significantly contributes to improving the quality and quantity of halal food production, supporting the sector’s growth, and strengthening Indonesia’s position as a global hub for the halal food industry.